USULAN PERBAIKAN TATA LETAK LINI INNER ASSEMBLING DENGAN SIMULASI SISTEM UNTUK MENGOPTIMALKAN KESEIMBANGAN LINI PRODUKSI MENGGUNAKAN METODE RANKED POSITION WEIGHTDI PT. PANASONIC MANUFACTURING INDONESIA (Jurnal Inovisi (Teknik Industri), 2017)
AbstractPT. Panasonic Manufacturing Indonesia is a company that produces electronic goods for household needs. One of them is the Refrigerator (refrigerator). The refrigerator production process is carried out in the inner assembling line. Based on the observations on the inner assembling production line, the problem that occurs is too high tacktime in the production process in the inner assembling line, then the inner assembling production line is not yet optimal. The layout of inner assembling is not optimal, causing a lot of work in process, inventory in process and many reject products. The purpose of this study is to optimize the balance of the inner assembling line by relaying the inner assembling production line and reducing tacktime on the production line. The method used is ranked position weight by increasing the efficiency of the inner assembling line from 49.95% to 81.56%. The monthly use of the machine costs Rp. 30,888,000.00 and the result is that after relaying the costs of using the overhead conveyor machine are no longer used.                                                                                                                                                           Keywords: inner assembling, work in process, inventory in process, conveyor overhead AbstrakPT. Panasonic Manufacturing Indonesia merupakan perusahaan yang memproduksi barang- barang elektronik untuk kebutuhan rumah tangga. Salah satunya adalah Refrigerator (kulkas). Proses produksi refrigerator dilakukan pada lini inner assembling. Berdasarkan hasil pengamatan pada lini produksi inner assembling masalah yang terjadi yaitu terlalu tingginya tacktime pada proses produksi di lini inner assembling, kemudian belum optimalnya keseimbangan lini produksi inner assembling. Adapun tata letak inner assembling yang kurang optimal sehingga menyebabkan banyaknya Work in process, inventory in process dan banyaknya produk yang reject. Tujuan penelitian ini adalah mengoptimalkan keseimbangan lini inner assembling dengan cara me-relayout lini produksi inner assembling dan mengurangi tacktime pada lini produksi. Metode yang digunakan yaitu ranked position weight dengan meningkatkan efisiensi lini inner assembling dari 49,95 % menjadi 81,56%. Pemakaian biaya mesin yang tiap bulan Rp.30,888,000,00,- dan hasilnya setelah di relayout biaya pemakaian mesin conveyor overhead tidak terpakai lagi.                       Kata kunci: inner assembling, work in process, inventory in process, conveyor overhead